O-183 Increased Risk Of Hypertensive Disorders Of Pregnancy In Hormone Replacement Therapy Cycle - A Multicenter Cohort Study In Frozen Blastocyst Transfer In Ovulatory Women. (6th August 2021) - Gu, F; Tan, M; Chen, Y; Li, X; Xu, Y
Abstract: Study question: Is hormone replacement therapy cycle (HRT) associated with a higher risk of adverse perinatal outcomes than natural cycle (NC) during frozen embryo transfer (FET)? Summary answer: Higher rates of hypertensive disorders of pregnancy (HDPs) and macrosomia were detected in HRT-FET as compared to NC-FET in ovulatory women.  What is known already: Live-birth rates after HRT-FET and NC-FET are found to be comparable. Recent data showed that pregnancies following HRT-FET are associated with higher risks of HDPs. However, the results might be influenced by selection bias as patients with ovulation disorder were more prone to receive HRT than ovulatory women. As is known, patients with ovulation disorder might have more endocrine disturbances than ovulatory women, which could be associated with adverse obstetrical outcomes. Study design, size, duration: Four large reproductive medical centers in Guangdong province, Southeast of China, took part in this multicenter retrospective cohort study. Patients with regular cycles (25-35 days), who underwent either HRT or NC blastocyst FET and delivered after 20 weeks of gestation between January 2017 and December 2019 were analyzed. Preimplantation genetic testing (PGT) cycles, multiple pregnancies and cases with type II diabetes or preconceptional hypertension were excluded. Each patient only contributed one cycle per cohort. Participants/materials, setting, methods: Treatment cycles from each patient were linked to their obstetrical medication record and a comprehensive chart review was done to investigate their perinatal outcomes. Maternal and neonatal outcomes were compared between NC-FET and HRT-FET cycles. Multiple logistic regression analyses were performed to adjust the confounding factors including baseline demographics (maternal age, BMI, education level, parity, type of infertility and cause of infertility), as well as IVF characteristics (insemination method and embryo cryopreservation duration). Main results and the role of chance: A total of 406 cases from NC-FET and 602 cases from HRT-FET were included. A multiple logistic regression analysis showed that pregnancies after HRT-FET had increased odds of HDPs [adjusted odds ratio (aOR) 2.44, 95% confidence interval (CI), 1.39–4.29] in comparison to pregnancies after NC-FET. Singletons born after HRT-FET were at increased risk of macrosomia compared to NC group (aOR 2.74, 95%CI 1.10–6.87). No significant difference could be seen regarding other obstetrical complications including gestational diabetes, placenta previa, placental abruption and postpartum hemorrhage between HRT-FET and NC-FET. No significant differences were noticed for preterm birth and low birthweight between the different endometrial protocols. Limitations, reasons for caution: Our study was retrospective in nature, and some cases were excluded due to missing data. Wider implications of the findings: Pregnancies following HRT-FET are associated with higher risks of HDPs and macrosomia in ovulatory women. Physicians should be cautious on the decision of the endometrium preparation for FET, especially for those who can ovulate normally. Trial registration number: 2018YFC100310